Religion and philosophy of N⁻al⁻ayira divya prabandham with special reference to Namm⁻alv⁻ar - Cuppu Reṭṭiyār, Na., 1917- (Sri Venkateswara University Tamil Dept. publication, 1977)
On the Nālāyirat tivviyap pirapantam, an anthology of Tamil devotional literature by the Vaishnav saints of South India (Alvars)